Management of Independent Middle Mesial Canal in Mandibular First Molar Using Cone Beam Computed Tomography Imaging as an Adjunct – A Case Report - Mahajan, Pardeep; Monga, Prashant; Goyal, Roma; Bajaj, Nitika (Journal of Baghdad College of Dentistry, 2016)
The primary objective of root canal therapy is adequate biomechanical preparation of root canal system followed by 3D obturation.in clinics we are encountered with several anatomical variations, which we need to manage efficiently. One of the major factors responsible for failure of root canal therapy is missed canals. Recent technological advances have given the clinician opportunity to identify anatomical variations and treat them to satisfaction.